PTU-108 Hyperferritinaemia (hf) – is it being investigated appropriately in the primary care setting?. (17th June 2017) - Meade, S; Coster, DA De; Mucha, P Vila De; Nayagam, J; Griffiths, K; Kashyap, M; Hughes, K; Curtis, H
Abstract : Introduction: Ferritin is an intracellular iron storage protein and reflects total body iron levels. As an acute phase protein, HF also occurs in pro-inflammatory states and metabolic disorders. Thus, further investigations are required to confirm iron overload. Approximately 10% of Caucasians with HF will have an underlying disease leading to iron overload. Early diagnosis and treatment is key to the prevention of end-organ damage. Method: A retrospective analysis of laboratory biochemistry data from between January and November 2015 was undertaken. During this period, a total of 890 individual patient results indicated significant HF (serum ferritin >500 µg/L). A sample of 200 patients was randomly selected from this group for further analysis. 17 patients were excluded due to duplication, death or relocation within 6 months of the index test. In the study group (n=183), the following data were analysed: patient demographics, historical and repeat ferritin levels, iron studies, liver function tests, full blood count, inflammatory markers, and HbA1c or glucose. Results: From the study group (n=183, ages 25–102 years), there were 70 females (38%) and 113 males (62%). An index ferritin level between 500–1000 ug/L was present in 79.2% of patients (moderate HF group, n=145) and >1000 ug/L in 20.8% patients (severe HF group, n=38). No iron studies were requested in 110/183 patients (60.1%) within 15 months of the index ferritin, or historically (63.5% vs 47.4% in the moderate and severe HF groups respectively). In 17/110 patients (15.5%), HF (>500 ug/L) had previously been identified but historical iron studies had been requested in only 5/17 (29.4%). Repeat ferritin levels following the index case were requested in 100/183 patients (52.4% and 63.2% moderate and severe HF respectively). 66/183 (36.1%) had no iron studies, at any time, or a repeat ferritin requested (39.3% and 23.7% in the moderate and severe HF groups respectively). In patients with requested iron studies (73/183, 39.9%), iron overload (transferrin saturations>45% for women and >50% for men) was identified in 7.1% (n=13/183, 4.8% and 15.8% of the moderate and severe HF groups respectively). Conclusion: This study has identified that significant HF is often inadequately investigated in the primary care setting. In our study group, no attempt was made to exclude iron overload in 54.6% of cases (n=100); either historically or within 15 months of finding HF. We believe that this study highlights the need for further education regarding the investigation of HF in primary care in order to reduce the risk of irreversible end-organ damage in patients with iron overload. Reference: . EASL. Clinical practice guidelines for HFE hemochromatosis. Journal of Hepatology2010;53:3–22 Disclosure of Interest: None Declared